The superfamily Plateremaeoidea (Acari: Oribatida) I. The family Plateremaeidae, Plateremaeus cebilae sp. nov. from Argentina and its ontogenetic development, and the new family Gaboneremaeidae - Fernandez, Nestor (2024)
This is the frst in a planned series of revisions of the superfamily Plateremaeoidea. A new species of Plateremaeidae, Plateremaeus cebilae sp. nov., is described from Argentina based on adults and immatures. This species is easily distinguishable from other congeners by: cerotegument covering body and legs; polyhedral structures of flaments on prodorsum, notogaster, epimeres, and ventral region; interlamellar setae covered by rose-fower-shaped cerotegument; sensillus uncinate; fve pairs of notogastral setae situated posteriorly; pedotectal tooth well visible; epimeral neotrichy 8[7-9]-5[4-6]-6[5-6]-8[7-9]; genital plate ovoid, with nine pairs of small barbate setae in two rows; anal plate elongated-ovoid, with fve pairs of setae; genito-anal bridge moderately developed. The ontogeny of this species is described.Gaboneremaeidae fam. nov. and Gaboneremaeus gen. nov. are established, with G. patriciae sp. nov. from Gabon as its type species. Gaboneremaeus patriciae sp. nov. is distinguished by: cerotegument of two types, covering body and legs; prodorsum with cuticular folds; bothridial ring sigmoid, complex; notogaster rounded, pleurophragma present; three pairs of posterior setae; posterior medial zone with small rounded pit; epimeral zone well delimited, with epimeric furrows, apodemes and cuticular thickening; parastigmatic enantiophysis and discidium present; epimeral hypertrichy 9[8-10]-6-9[8-10]-9[8-11]; nine pairs of barbate genital setae in two rows; anal plate with ten pairs of setae inserted in paraxial groove of each valve.